Visible-light photovoltaic effect in high-temperature ferroelectric BaFe4O7. Issue 45 (28th October 2020) - Zhang, Ganghua; Hou, Jingshan; Zhu, Mingjun; Huang, Guoquan; Li, Dezeng; Fang, Yongzheng; Zeng, Tao
Abstract : A new high-temperature ferroelectric BaFe4 O7 without volatile elements has been presented with a visible-light photovoltaic effect. Abstract : Ferroelectric photovoltaics, as a new type of solar cell, relying on an internal electric field instead of p–n or Schottky junctions, can considerably improve the efficiency of charge separation and migration. But, non-volatile elements containing ferroelectrics with narrow bandgaps and excellent photoelectric performances are still scarce. Herein, a new ferroelectric compound, BaFe4 O7, has been synthesized by a conventional hydrothermal method. A polar trigonal structure ( P 31 c ) was proposed by X-ray diffraction (XRD) and transmission electron microscopy (TEM) analyses. UV-vis-NIR diffuse reflectance spectrum revealed a visible-light bandgap E g of 2.18 eV. Intrinsic ferroelectricity with a high Curie temperature ( T c ∼ 791 K) was confirmed by dielectric and ferroelectric measurements. The electrical saturation polarization ( P s ), remanent polarization ( P r ) and coercive field ( E c ) were determined as 6.34 μC cm −2, 3.32 μC cm −2 and 42.38 kV cm −1 respectively. A bulk photovoltaic effect was observed in the poled sample with a steady-state photocurrent of 39 nA cm −2 and photovoltage of 0.19 V under standard AM 1.5G illumination, which demonstrated its promising applications in photoelectric devices.